ARLOKA MAP: MEDIA PENGENALAN NILAI-NILAI KEARIFAN LOKAL DI KAWASAN CANDI PRAMBANAN - Yusuf, Sandy Maulana; Syarqiyah, Indah Nurafani; Arrazaq, Naufal Raffi (Berkala Arkeologi, 2019)
Abstract Prambanan Temple contains local wisdom values that have not been well informed to domestic visitors. This article aims to introduce Arloka Map, an alternative communication media in a form of physical tour-map containing local wisdom values of the Prambanan Temple Area and to test the effectiveness rate of the Arloka-Map. Observation, literature studies, and instrument test methods were used to collect basic data. To determine the success rate of the proposed strategy, pre- and post-tests were conducted to 50 domestic tourist respondents. The outcomes were then analyzed by using the SPSS application. Results showed that score for visitors that were using the Arloka-Map was higher than visitors who did not use it (i.e. 8.72 vs 4.44). It was concluded that the use of the Arloka-Map assist tourists to know the values of local wisdoms at the temple's area.